Patterns of Forest Encroachment Behavior Based on Characteristics of Immigrants and Local Communities - Yurike Yurike; Yonariza Yonariza; Rudi Febriamansyah (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
This study aims to analyze the comparison of the behavioral characteristics of forest encroachers between migrants and local communities. The research method uses descriptive analysis. Sampling using the snowball sampling method. The results showed that the behavior of forest encroachment was formed based on the number of respondents from the most, namely the behavior of sustainable, mixed and unsustainable use. However, when viewed based on land area, it turns out to be inversely proportional to where the area of rubber plantations is at least 822 ha, while the area of oil palm plantations reaches 1203 ha. In addition, it should be noted that the highest land area is found in a mixed pattern. This means that local people have started to look at oil palm plantations for cultivation. Overall, based on the age that dominates the forest encroachers, the range is 31-50 years. The education of migrants is higher than that of local communities, but the pattern of encroachment of local communities is more sustainable when compared to migrants. The number of family members of immigrants is mostly in the medium category, while the number of family members of local communities is mostly in the small category. In addition, squatters whose main occupation is farmers tend to be more sustainable when compared to other occupations. Efforts to resolve the problem of forest encroachment in the Dharmasraya PFMU area can be resolved through sustainable community empowerment activities, improving the handling of encroachers, and increasing the effectiveness of PFMU management.